2010
DOI: 10.1093/cercor/bhp312
|View full text |Cite
|
Sign up to set email alerts
|

Response Profile of the Face-Sensitive N170 Component: A Rapid Adaptation Study

Abstract: To study the response profile of the face-selective N170 component, an adaptation procedure was employed where adaptor and test stimuli were presented in rapid succession. Test stimuli came from 4 different face categories (upright, inverted, and eyeless faces and eyes-only images). The same face stimuli, as well as upright and inverted houses, served as adaptors. Strong N170 amplitude reductions indicative of adaptation were found for all types of face test stimuli preceded by face adaptors relative to house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
153
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(185 citation statements)
references
References 31 publications
28
153
3
1
Order By: Relevance
“…The N170 response to eyeless faces would also reflect the sole response of face neurons which seems optimal when eyes are present as reflected by shorter latency to faces than eyeless faces. This model, and in particular the idea that eye neurons are inhibited in response to upright but not inverted faces, was recently supported by an adaptation study (Eimer et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…The N170 response to eyeless faces would also reflect the sole response of face neurons which seems optimal when eyes are present as reflected by shorter latency to faces than eyeless faces. This model, and in particular the idea that eye neurons are inhibited in response to upright but not inverted faces, was recently supported by an adaptation study (Eimer et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…Several studies using priming or habituation paradigms have shown reduced N170 amplitude (or M170 amplitude in MEG studies) in response to faces that were preceded by faces compared to non-face stimuli [74,[77][78][79][80][81] . These repetition suppression or adaptation effects are typically taken as evidence that the preceding stimulus and following stimulus activate a common neuronal representation at Inversion Enhanced amplitude and/or delayed latency [87,[99][100][101] Reduced amplitude [98] Delayed repetition effects [95] Contrast-reversal Enhanced amplitude [99] Repetition effects spread over longer time-window [95] Eye removal Similar amplitude for complete faces and faces with -eyes removed [86] No effects of inversion or contrast-reversal for faces -with eyes removed [103] Isolated eyes Similar or enhanced amplitude compared to intact faces [87] Holistic processing Shorter latency for repeated face halves in aligned faces [110] Longer latency for aligned compared to misaligned face halves [110] Less repetition suppression to aligned face stimuli for -half-identical or completely new faces compared to identical faces [111] Second-order relational processing Conflicting evidence on the effects of thatcherization on -processing of upright and inverted faces [114][115][116] Larger amplitude for configurally than featurally altered faces over the right hemisphere [117] Stimulus repetition Repetition suppression.…”
Section: The Neurophysiology Of Face Processingmentioning
confidence: 99%
“…Reduced amplitude for repetition Repetition enhancement. Enhanced amplitude for repetition of different [74,77,80,81] or same faces [94] of same faces [88,91,92] Fig and profile-view faces has been taken as evidence that a view-invariant representation of faces is accessed in both cases [82] .…”
Section: The Neurophysiology Of Face Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude increase with inversion, also termed the N170 "face inversion effect" (FIE), is thus believed to reflect the disruption of early holistic processing stages specific to human faces and has been used as a hallmark of face specificity. At the neuronal level, this increase has been explained by the recruitment, in addition to face-sensitive neurons, of object-sensitive neurons (Itier & Taylor, 2002;Rossion et al, 1999;Sadeh & Yovel, 2010;Yovel & Kanwisher, 2005), other facesensitive neurons tuned to the inverted orientation (Eimer et al, 2010), or eye-sensitive neurons (Itier et al, 2007). Itier et al (2007) showed that, in contrast to intact faces, inversion of eyeless faces elicited a much reduced N170 FIE and thus proposed that eyes played an important role in this early face specific phenomenon, an idea reinforced by the replication of this finding in later studies Kloth et al, 2013;Nemrodov & Itier, 2011).…”
Section: Introductionmentioning
confidence: 99%